Efektivitas Penggunaan Teknik Pembelajaran Google Classroom Berbantuan Whatsapps dalam Pembelajaran IPA - Sunaryo Romli (Direktorat Guru Pendidikan Dasar, Kemendikbudristek R.I., 2022)
Scientific numeracy literacy is the knowledge and ability to use a variety of numbers and symbols related to basic mathematics to solve practical problems in various contexts of everyday life. Numerical literacy also includes the knowledge and skills to analyze scientific information presented in various forms (graphs, tables, charts, etc.) and then use the interpretation of the results of the analysis to predict and draw conclusions and decisions. This study aims to determine the effectiveness of learning using Google Classroom (GCR) assisted by WhatsApp (WA) on the scientific numeracy literacy skills of students in the Caloric material. Type of this research is development research using the ADDIE model with the type of research design pretest-posttest one group design involving 2 classes of seventh grade students consisting of 50 students in a junior high school in Bandar Lampung City. The research instrument was in the form of a scientific numeracy literacy test for the Caloric material. Data analysis using n-gain test. The results of the scientific numeracy literacy test showed that learning using Google Classroom assisted by WhatsApp obtained n-gain values ​​in the experimental class of 0.66 and 0.57 (medium category). These results indicate that the learning technique using Google Classroom assisted by WhatApps is effectively used in online learning during the Covid 19 pandemic.